Kondo effect goes anisotropic in vanadate oxide superlattices. (7th October 2015) - Rotella, H; Pautrat, A; Copie, O; Boullay, P; David, A; Mercey, B; Morales, M; Prellier, W
Abstract: We study the transport properties in SrVO3 /LaVO3 (SVO/LVO) superlattices deposited on SrTiO3 (STO) substrates. We show that the electronic conduction occurs in the metallic LVO layers with a galvanomagnetism typical of a 2D Fermi surface. In addition, a Kondo-like component appears in both the thermal variation of resistivity and the magnetoresistance. Surprisingly, in this system where the STO interface does not contribute to the measured conduction, the Kondo correction is strongly anisotropic. We show that the growth temperature allows a direct control of this contribution. Finally, the key role of vanadium mixed valency stabilized by oxygen vacancies is enlightened.